Fenomena Penggunaan TikTok Pada Mahasiswa UIN Shulthan Thaha Saifuddin Jambi - Dila Mayang Sari; Ahdiyat Mahendra (Prodi Bimbingan dan Konseling Islam (BPI) Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2021)
The Tik Tok app is a Chinese social network and music video platform. which was launched in September 2016. This application is a short video creation application with the support of music, which is very popular with many people including adults and minors. The existence of teenagers is important in socializing. The existence of teenagers is also a symbol that a teenager can get along and choose connections with other people. Because existence is often connoted with pleasant things. For example, having lots of friends and connections, being an important person and some of the pleasures of being with another teenager like being able to express himself freely and doing things that have become a trend for other teens. This is what makes the lifestyle of teenagers in general change. They try to always exist so that sometimes they are too excessive and wrong in seeking their existence. This study uses a qualitative research with a phenomenological approach, and the location of this research was carried out at the Shulthan Thaha Saifuddin State Islamic University Jambi. The data that has been collected is then analyzed using a qualitative descriptive method. From this study it was found that the use of the Tik Tok application by students of the State Islamic University of Sulthan Thaha Saifuddin Jambi can be divided into 3 groups, namely using the Tik Tok application for expression, using the Tik Tok application to seek entertainment and relieving fatigue / boredom, and only having an account but not using the Tik Tok application. intense use and do not upload video content. While the motive for using the Tik Tok application for students at the State Islamic University of Sulthan Thaha Saifuddin Jambi is as a medium to express themselves, fill spare time and learn to be confident and make interesting videos.